Involvement of Epidermis Cell Proliferation in Defense Against Beauveria bassiana Infection - Huang, Wuren; Tang, Ruijuan; Li, Shirong; Zhang, Ying; Chen, Rongbing; Gong, Liyuan; Wei, Xuefei; Tang, Yingyu; Liu, Qiuning; Geng, Lei; Pan, Guoqing; Beerntsen, Brenda T.; et al. (Frontiers in Immunology, 2021)
Entomopathogenic fungi Beauveria bassiana can infect many species of insects and is used as a biological pesticide world-wide. Before reaching the hemocoel, B. bassiana has to penetrate the integument which is composed of a thick chitin layer and epidermal cells. Some chitinase, protease and lipase secreted by B. bassiana are probably involved in the fungal penetration of the integument. While microscopic proof is needed, it is difficult to locate the precise infection sites following the traditional method of immersion infection. Consequently, we developed a new method to inoculate conidia solution into a single fixed-site on the back of one segment. This fixed-site infection method is pathogenic but it is also dose dependent. Using the fixed-site infection protocol, it is also very convenient to track hyphae inside the cuticle layer by light and transmission electron microscopy. The fact that few hyphae were detected inside the chitin layer after fixed-site infection with mutant ∆BPS8, a protease secreted during fungi germination, indicates that this method is suitable for screening genes involved in penetrating the integument in large scale. We also found that melanization occurs before new hyphae penetrate the chitin layer. Most importantly, we discovered that fungal infection can induce epidermal cell proliferation through DNA duplication and cell division, which is essential for the host to defend against fungal infection. Taken together the fixed-site infection method may be helpful to determine the mechanism of fungal and host interaction in the integument so as to effectively exert fungal biological virulence.